Physical activity, cardiorespiratory fitness, and clustered cardiometabolic risk in 10‐ to 12‐year‐old school children: The REACH Y6 study. Issue 4 (6th March 2014) - Boddy, Lynne M.; Murphy, Marie H.; Cunningham, Conor; Breslin, Gavin; Foweather, Lawrence; Gobbi, Rebecca; Graves, Lee E.F.; Hopkins, Nicola D.; Auth, Marcus K.H.; Stratton, Gareth
ABSTRACT Objectives (1) Investigate whether clustered cardiometabolic risk score, cardiorespiratory fitness (CRF), sedentary time (ST), and body mass index Z‐scores (BMI Z‐scores), differed between participants that met and did not achieve ≥60 min of daily moderate to vigorous intensity physical activity (MVPA). (2) Compare clustered cardiometabolic risk score, BMI Z‐score, ST, and MVPA by CRF status. Methods One hundred and one (n = 45 boys) 10‐ to 12‐year‐old participants took part in this cross‐sectional study, conducted in Liverpool (Summer 2010) and Ulster (Spring 2011) UK. Assessments of blood markers, stature, sitting stature, body mass, waist circumference, flow mediated dilation (FMD), and resting blood pressure (BP) were completed. CRF (VO2 peak) was estimated using an individually calibrated treadmill protocol. Habitual MVPA and ST were assessed using an individually calibrated accelerometer protocol. Clustered cardiometabolic risk scores were calculated using blood markers, FMD (%), BP and anthropometric measures. Participants were classified as active (≥60 min MVPA) or inactive and as fit or unfit. Multivariate analysis of covariance (MANCOVA) was used to investigate differences in cardiometabolic risk, BMI Z‐score, CRF, and ST by activity status. MANCOVA was also completed to assess differences in cardiometabolic risk, MVPA, ST, and BMI Z‐score by fitness status. Results Inactive children exhibited significantly higher clustered cardiometabolic risk scores and ST, and lower CRF than active children. Unfit participants exhibited significantly higher clustered cardiometabolic risk scores, BMI Z‐scores and ST and lower MVPA in comparison to fit participants. Conclusions This study highlights the importance of children achieving 60 min MVPA daily and provides further evidence surrounding the importance of CRF for health. Am. J. Hum. Biol. 26:446–451, 2014. © 2014 Wiley Periodicals, Inc.